(untitled) (American Journal of Islam and Society, 1991)
This is a wide-ranging and fascinating collection of papers dealing with the impact of religion on what may be called the social economy. It is an ecumenical volume in that it begins with the Catholic Church then considers severaJ forms of Protestantism, then goes on to discus Judaism, and finally considers Islam. It should be clear that the volume is predominantly "Christian," but the effort to include the other monotheistic religions is very welcome. One difficulty in reviewing this volume is that many of the papers are informative but not representative of the religious traditions they represent. Thus A. M. C. Waterman’s piece describes a particular phase of Anglican social thought, and the same is true of the one by Paul Heyne. Perhaps an overview is po ible only for those movements which are no longer active, a in Ronald Preston’s fine contribution on Christian Socialism in Britain. I must confess some surprise on finding the vigor with which any perceived defect of the market was defended. For Muslims, some of the most interesting points about this volume are to be found in the instances of active politicians who took strong religious stands. Abraham Kuyper’s vision of neo-Calvinism is the outstanding example in the paper by Bob Goudzwaard, but Waterman’s presentation of Prime Minister Margaret Thatcher’s views are equally revealing. Of less practical import, but nonetheles equally intriguing, is the account by John Yoder of the "First Reformation" in Czechoslovakia as well as the reasons for the neglect of this movement-lack of political support, linguistic distance from We tern Europe, and an ab ence of shared doctrinal formulations. The description of Judaism and the Market Mechanism by Meir Tamari provides many parallels with Islamic market supervi ion, and there is even ...